2014
DOI: 10.1523/jneurosci.0511-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Egocentric and World-Centered Reference Frames in the Rat Posterior Parietal Cortex

Abstract: Navigation requires coordination of egocentric and allocentric spatial reference frames and may involve vectorial computations relative to landmarks. Creation of a representation of target heading relative to landmarks could be accomplished from neurons that encode the conjunction of egocentric landmark bearings with allocentric head direction. Landmark vector representations could then be created by combining these cells with distance encoding cells. Landmark vector cells have been identified in rodent hippoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
278
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(319 citation statements)
references
References 70 publications
29
278
4
Order By: Relevance
“…Our results resonate with the view that rodent PPC encodes combinations of spatial attributes (McNaughton et al, 1994;Nitz, 2006Nitz, , 2012Save andPoucet, 2000, 2009;Whitlock et al, 2012;Wilber et al, 2014). Specifically, we found that the activity of PPC neurons can be accurately predicted based on two extremely simple spatial measures: position of the animal along the corridor, and heading direction.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results resonate with the view that rodent PPC encodes combinations of spatial attributes (McNaughton et al, 1994;Nitz, 2006Nitz, , 2012Save andPoucet, 2000, 2009;Whitlock et al, 2012;Wilber et al, 2014). Specifically, we found that the activity of PPC neurons can be accurately predicted based on two extremely simple spatial measures: position of the animal along the corridor, and heading direction.…”
Section: Discussionsupporting
confidence: 88%
“…A complementary set of studies performed in rodents suggested an important role of PPC in spatial navigation (McNaughton et al, 1994;Nitz, 2006Nitz, , 2012Save andPoucet, 2000, 2009;Whitlock et al, 2012;Wilber et al, 2014). Rat PPC encodes combinations of spatial location and body movement (McNaughton et al, 1994;Nitz, 2006Nitz, , 2012Whitlock et al, 2012;Wilber et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A little more than half of the cells were also place cells, but a substantial fraction did not have any significant tuning to place. Cells with essentially the same characteristics were recently reported in posterior parietal cortex 17 . Goal-vector cells are reminiscent of cells reported in rats in earlier hippocampal studies, in which neural firing increased in the proximity of a goal 73,[221][222][223][224][225] , and the finding of goal-orientation cells in both parietal cortex and hippocampus begs the question of which region is 'copying' which.…”
Section: Co M M E N Ta Rysupporting
confidence: 81%
“…Navigation in an idiothetic reference frame is often referred to as 'path integration' , a process by which animals use self-motion cues (such as motor efference, optical flow, and vestibular information) to keep track of their own location relative to a starting point [11][12][13][14] . Decades of investigation have shown that egocentric space is not represented primarily in the hippocampal formation but rather in parietal cortex and associated regions [15][16][17] . O'Keefe's studies showed from the outset that, instead, place cells encode an animal's location in an Although the study of the cellular and circuit mechanisms of spatial representation in the brain today is centered on the hippocampal and parahippocampal formation, the study of spatial coding did not begin there, but rather began with the parietal cortex, in the form of early observations on patients with parietal damage 1,2 ; in many respects, one takes a risk in attempting to limit the discussion to the hippocampal formation 3 .…”
Section: Volume 20 | Number 11 | November 2017 Nature Neuroscience C mentioning
confidence: 99%